ANALISIS HADIS TENTANG AMAL BERKELANJUTAN DAN PENDIDIKAN SALAT BAGI ANAK - Abidin, Zainal (State Institute of Islamic Studies (IAIN) Palu, 2008)
Islam asserts that whatever Muslims do in this world will give impacts to their life in the hereafter. However, not all good deeds that muslims have performed so far in this world will always give incessant rewards, particularly for the deceased, except for three things as stated in the Prophetic hadîth: sadaqah jâriyyah (charity), beneficial knowledge for others, and good descendants who always pray for them. These categories are still debated by some scholars. Therefore, this paper is intended to study this hadîth in order to reveal its validity.Kata Kunci: hadis, amal berkelanjutan, pendidikan salat, hujjah